Uso del Blog como Material Didáctico para la Enseñanza de la Historia: Desarrollo del Pensamiento Crítico desde la Vida de Guadalupe Salcedo y la Historia de los Llanos Orientales en los Años Cincuenta. (2022)
This degree work is focused on enhancing knowledge and knowledge in ninth grade high school students, through a digital teaching material, which guides the theme of Guadalupe Salcedo and the liberal guerrillas of the eastern plains in the mid-twentieth century in Colombia.